Production of Ag nanoparticles Using Aloe vera Extract and its Antimicrobial Activity - Hashoosh, Sarah Ibrahim; Fadhil, Ayad M A; Al-Ani, Nabeel K (Al-Nahrain Journal of Science, 2018)
The study was carried out to explain the role of Aloe vera extract as a reducing agent for the production of Ag nanoparticles. The UV-VIS spectrophotometer showed shift peak at 400nm and scanning electron microscope (SEM) showed the rectangular morphology of as prepared Ag nanoparticles with a size of (500) nm. These nanoparticles gave significant effect on Gram negative bacteria E.coil and Gram positive bacteria S.aureus at concentration 3.5 mgml, but it did not have any antifungal effect on Candida albican, Pencillium spp and Aspergillas niger.